>
其他
>
4(2p+3q)^2-9(3p-q)^2 因式分解
人气:310 ℃ 时间:2020-01-24 16:45:02
解答
4(2p+3q)^2 - 9(3p-q)^2
=[2(2p+3q) + 3(3p-q)][2(2p+3q) - 3(3p-q)]
=(4p+6q+9p-3q)(4p+6q-9p+3q)
=(13p+3q)(9q-5p)
推荐
因式分解:4(2p+3q)^2-9(3p-q)^2
4(2p+3q)^2-(3p-q)^2 因式分解
4(2p+3q)的平方—9(3p-a)的平方 因式分解
因式分解:(1)4(2p+3q)^2-9(3p-q)^2 (2)(a+b+c)^2-(a-b-c)^2 (^2代表平方)
分解因式:4(2p+3q)^2-(3p-q)^2
两数和为3,积为-10 求这两个数
用英语简单描写你的房间
以我的卧室写一篇英语作文
猜你喜欢
carefully
After paying 1000 dollars ____,you will all become full memebers of our club A each B all c every
Our class has a map of the world (改为同义句)
The baby didn't cry any more when she saw her mother.同义句
How do you go to school,on foot or by bus?
时间旅行的悖论
设f(x)=ax7+bx5+cx3+dx+5,其中a,b,c,d为常数.若f(-7)=-7,则f(7)=_.
计算1-3+5-7+9-11+…+97-99.
© 2024 79432.Com All Rights Reserved.
电脑版
|
手机版